PENGEMBANGAN MODEL ANDREASSEN DAN ARTIFICIAL NEURAL NETWORKS MULTI VARIABEL UNTUK PREDIKSI FATALITAS LALULINTAS JALAN PADA WILAYAH PERKOTAAN DI JAWA BARAT - Agus, Supratman (Jurnal Transportasi, 2013)
Law Number 22 Year 2009 stated that fatality data must be completed with data from hospitals. However, the data reported by the Police of the Republic of Indonesia has not been in accordance to the law. In many countries researchers have been using population and motor vehicles numbers as variables to predict the number of fatalities. Those variables are not fit with Indonesian condition. The main purpose of this study was to develop better fatality prediction model in line with Indonesian condition. This was done by developing multivariable Andreassen and ANN models. The model was built by using population data taken from 8 cities in West Java Province. The main results from model validation test are: (1) three variables ANN with one hidden layer prediction model was the best prediction used for predicting the number of fatalities, (2) the number of fatalities was 122.8% larger than that reported by the Police, and (3) Andreassen prediction model was unfit to be used in Indonesia.